Cuckoo Search Approach for Cutting Stock Problem - Shair, Ezreen Farina; Khor, Shen Young; Abdullah, Abdul Rahim; Jaafar, Hazriq Izzuan; Saharuddin, Nur Zawani; Zainal Abidin, Amar Faiz (International Association of Computer Science and Information Technology Press (IACSIT Press), 2015)
Cutting Stock Problem has been used in many industries like paper, glass, wood and etc. Cutting Stock Problem has helped industries to reduce trim loss and at the same time meets the customer’s requirement. The purpose of this paper is to develop a new approach which is Cuckoo Search Algorithm in Cutting Stock Problem. Cutting Stock Problem with Linear Programming based method has been improved down the years to the point that it reaches limitation that it cannot achieve a reasonable time in searching for solution. Therefore, many researchers have to turn to metaheuristic algorithms as a solution to the problem which also makes these algorithms become famous. Cuckoo Search Algorithm is selected because it is a new algorithm and outperforms many algorithms. Hence, this paper intends to experiment the performance of Cuckoo Search in Cutting Stock Problem.